2010
DOI: 10.1124/jpet.110.170605
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Docosahexaenoic Acid, but Not Eicosapentaenoic Acid, Delays Ca2+-Induced Mitochondria Permeability Transition in Normal and Hypertrophied Myocardium

Abstract: Intake of fish oil containing docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) prevents heart failure; however, the mechanisms are unclear. Mitochondrial permeability transition pore (MPTP) opening contributes to myocardial pathology in cardiac hypertrophy and heart failure, and treatment with DHA ϩ EPA delays MPTP opening. Here, we assessed: 1) whether supplementation with both DHA and EPA is needed for optimal prevention of MPTP opening, and 2) whether this benefit occurs in hypertrophied myocardiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 24 publications
6
51
5
Order By: Relevance
“…DHA has known effects in the TAC model, including inhibition of mitochondrial transition pore opening ( 45,46 ), but whether this improves survival is not clear ( 45 ). Our data suggest that EPA-mediated prevention of fi brosis does not completely reverse diastolic dysfunction ( Fig.…”
Section: Ffar4 Was Required To Prevent Tgf ␤ 1-induced Fi Brosis In Pmentioning
confidence: 67%
“…DHA has known effects in the TAC model, including inhibition of mitochondrial transition pore opening ( 45,46 ), but whether this improves survival is not clear ( 45 ). Our data suggest that EPA-mediated prevention of fi brosis does not completely reverse diastolic dysfunction ( Fig.…”
Section: Ffar4 Was Required To Prevent Tgf ␤ 1-induced Fi Brosis In Pmentioning
confidence: 67%
“…MPTP opening was inferred from the sudden and large increase of fluorescence. Mitochondrial Ca 2ϩ tolerance was defined as the cumulative Ca 2ϩ load that was required to induce the abrupt increase in extramitochondrial Ca 2ϩ from a semilog plot (47).…”
Section: Methodsmentioning
confidence: 99%
“…Their effects have been studied on cardiac and skeletal muscles, but with limited focus on mitochondrial function. It has been reported that n-3 polyunsaturated fatty acids increase cardiac mitochondrial calcium retention capacity without any change in oxygen consumption (32,45). However, the combination of DHA and EPA and the use of marine oil have been reported to have less profound effect compared with DHA alone (33).…”
mentioning
confidence: 99%